Bimbingan Pra NIkah dan Pemahaman Peran Suami Istri di KUA Kecamatan Sakra - Riadi, Taufiq (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2024)
ABSTRACT Premarital guidance is assistance provided to prospective brides and grooms to analyze possible problems and challenges that will arise in their household and equip them with the skills to solve problems. The aim of this research is to find out the impact of premarital guidance on understanding the role of husband and wife in the KUA of Sakra sub-district, how the process of implementing pre-marital guidance is carried out and what are the obstacles to the effectiveness of pre-marital guidance for Catin (bride and groom). The type of research used in this research is a qualitative approach field research. Data collection techniques used in this research were interviews, observation and documentation. Then the data analysis techniques used in this research include data reduction, data presentation and drawing conclusions. Meanwhile, the data validity technique used in this research uses source collation. The research results obtained are that pre-marital guidance is very influential and has a big impact on understanding the role of husband and wife. The process followed in implementing premarital guidance is to first register with the KUA and then later the KUA will provide a summons for pre-marital guidance. The obstacles experienced include internal and external ones, obstacles from the KUA and obstacles from guidance participants. Keywords: Understanding Roles, Pre-Marital Guidance